The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmicb.2020.01988
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New High-Cell Density Fermentation Strategy for Enhanced Production of a Fungus β-Glucosidase in Pichia pastoris

Abstract: Liu et al. β-Glucosidase Production in Pichia pastoris unique information on cell growth, substrate metabolism and protein biosynthesis for enhanced β-glucosidase production using a P. pastoris strain under controlled fermentation conditions. This information may be applicable for expression of similar proteins from P. pastoris strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…obtained a specific activity of about 9 U mg –1 (pNPG) by recombinant expression of β-glucosidase in K. phaffii . Compared to the recent reports, the K.…”
Section: Resultsmentioning
confidence: 83%
“…obtained a specific activity of about 9 U mg –1 (pNPG) by recombinant expression of β-glucosidase in K. phaffii . Compared to the recent reports, the K.…”
Section: Resultsmentioning
confidence: 83%
“…Agitation and aeration may often cause excessive foam formation and thus influence cell growth and biotransformation efficiency. In our previous study, a certain quantity of antifoam reagent was added into the fermentation medium and reaction broth for the SmF of yeast and recombinant enzyme catalysis, respectively. The antifoam reagent has been used commonly in SmF, and the mechanisms of action were also summarized, such as bridging-stretching, spreading fluid entrainment, bridging-dewetting, etc . However, there is very little knowledge on the effect of antifoam reagent addition on the growth of Fusarium strains.…”
Section: Resultsmentioning
confidence: 99%
“…Other P AOX1 -regulated P. pastoris systems for secretory recombinant protein production normally claim a protein yield ranging from milligrams to grams per liter of culture with methanol induction. [29,30] For example, Gurramkonda et al [31] reported a yield of 3.1 g/L insulin precursor in the broth of a 15 L bioreactor through fedbatch fermentation; Werten et al [32] presented a study on improved secretion of recombinant gelatins through fedbatch fermentation in bioreactors ranging from 1-140 L, and the 15-copy transformant was able to produce an unprecedented high yield of 14.8 g gelatin per liter of clarified broth. Therefore, P. pastoris is a very robust expression system for high-yield recombinant protein production.…”
Section: Statements and Declarationsmentioning
confidence: 99%